PENGGUNAAN MEDIA GAMBAR PETA UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN IPS MATERI IDENTIFIKASI KONDISI GEOGRAFIS INDONESIA PADA SISWA KELAS 5 SD - Rozaqiyah, Honifah (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2019)
This study aims to improve student learning outcomes in the social studies subject matter to identify Indonesia's geographical conditions through the media of map images in grade 5 elementary school students. This research is motivated by students who are less enthusiastic in learning which causes students to be inactive in the learning process in the classroom, which sometimes can happen due to external and internal factors. So that in this case the teacher is required to design appropriate learning facilities to make students more attractive and understand what the teacher says. This research is a research and development or Research and Development (R&D). Borg and Gall. The results showed that there was an increase in student learning outcomes in the subject of social studies, identifying the geographical conditions of Indonesia based on maps through media images for grade 5 elementary school students. Based on the results of this study, it can be concluded that it is important for teachers to have technological literacy to develop their skills in using various media as supporting learning so that students are able to understand the material properly and correctly so as to improve student cognitive.